Analisis Pemahaman Al-Ghazali dan Abu Thalib Al-Makky Terhadap Struktur Keilmuan PAI - Meiviani Nurul Aisyah Maulana; Fitri Aulia; Irawan Irawan (STIKes Ibnu Sina Ajibarang, 2025)
Islamic education plays a crucial role in shaping the character and morality of Muslims. This study discusses the views of Imam Al-Ghazali and Abu Thalib Al-Makki regarding hadith in the context of religious education, as well as their contributions to the structure of Islamic Education (PAI) knowledge. The method used is library research with a descriptive qualitative approach, analyzing primary and secondary sources. The discussion results show that Al-Ghazali emphasizes the division of knowledge into fardhu 'ain and fardhu kifayah, while Al-Makki highlights the importance of intention in seeking knowledge. Both agree that Islamic education should integrate intellectual and spiritual aspects to form balanced and character-driven individuals.